Utilization of Ceramic Membrane Technology Based on Fluid Mechanics for Reducing COD, TDS, and TSS in Batik Wastewater - Arnesya Ramadhani; Frida Amriyati Azzizzah; Happy Ayu Puspa Sari; Badril Azhar (Postgraduate, University of Mataram, 2025)
This study utilizes ceramic membrane technology with the best composition based on the principles of fluid mechanics to reduce pollutant levels, especially COD, TDS, and TSS in batik waste. Ceramic membranes were synthesized using activated fly ash and kaolin as the main ingredients with variations in the material composition ratio of 30:70, 50:50, 70:30 (fly ash: kaolin), sintering temperatures used were 750 °C and 950 °C. Membrane performance was evaluated based on its flux and efficiency in reducing COD, TDS, and TSS using a batch filtration system. The results showed that membranes with a 70:30 fly ash to kaolin composition ratio achieved optimal pollutant reduction, using both sintering temperatures of 750 °C and 950 °C. The 70:30 ratio (fly ash : kaolin) and sintering temperature of 750 °C (L3) reduced COD by 57%, TDS by 13%, and TSS by 93%, while the 70:30 ratio (fly ash : kaolin) and sintering temperature of 950 °C (L6) reduced COD by 52%, TDS by 12%, and TSS by 95%. This research also demonstrates the application of physics principles, especially in fluid mechanics and material properties, which can serve as contextual learning materials and strengthen the understanding of applied physics in industrial practice.